PERUBAHAN PERILAKU TANAH EKSPANSIF AKIBAT STABILISASI DENGAN DSM BERPOLA TRIANGULAR MENGGUNAKAN KAPUR KADAR 8% - Rachmansyah, Arief; Zaika, Yulvi; Dharmawan, Aditya Leo (Jurnal Mahasiswa Jurusan Teknik Sipil, 2017)
Expansive clay has a high potential of shinkrage in case of changes in water contents. It can cause some damage to wall of building and cracks in the road.  There are some methods of soil stabilisation that already known, such as Deep Soil Mixing. DSM is a method using coloumn which contain soil mixing with material, it use variety of configuration that includes space of coloumn (L) and depth of coloumn (Df). Purpose of this research is to increasing bearing capacity and reducing swelling potential with DSM method in Ngasem, Bojonegoro for purpose of pavement construction. This research using 8% lime with triangular configuration with diameter of coloumn (D) is 3,2 cm. It uses variety space of coloumn (L) which is 1D, 1,25D and 1,5D and uses variety depth of coloumn which is 10 cm, 15 cm and 20 cm. Some test are required to determine characteristic of soil sample, such as spesific gravity, atteberg limit, clasification of soil based on USCS and standar compaction. To determine bearing capacity of soil it use loading test, and for test to determine swelling potential is based on ASTM 4546-86. Sample of soil is clasified as CH (anorganic clay with high plastisity). Result of this research proved that 8% lime can improve bearing strength and reduce swelling. Ratio of stabilisation soil is a important factor that determine improvement of bearing strength and swelling. Changes of depth (Df) will slightly give a higher improvement of bearing strength than changes of spacing (L). Triangular configuration which using space of coloumn (L) 3,2 cm and depth of coloumn (Df) 20 cm will give the most high value of improvement with 243,077% and reducement of swelling with 94,098 %. This variety of configuration can be use for flexible pavement as subgrade layer. Keywords: Expansive Soil, Deep Soil Mixing, Soil Stabilisation, Bearing Capacity, Swelling